La comunicación intercultural en la práctica pedagógica de los docentes de las instituciones educativas Maynas y Ramón Castilla y Marquesado, Iquitos 2023 - Zumaeta Moncayo, Wilton Richard (2025)
The main objective of the research was: Determine the level of intercultural communication in the pedagogical practice of teachers at the Maynas and Ramón Castilla y Marquesado Educational Institutions. The research assumed a quantitative approach, comparative descriptive type and design. The population was made up of teachers from the Ramón Castilla and Marquesado educational institutions, the sample was 150 teachers, 75 from each IE, considering professionals of both sexes. We worked with the survey technique and the questionnaire as a data collection instrument. The most important results of the study show that the sex of 150 (100.0%) teachers from the educational institutions, Maynas and Ramón Castilla y Marquesado, is mostly male 52.7% (79) compared to 47.3% ( 71) of the female sex. The level of intercultural communication, according to sex of the teachers of the educational institutions of Maynas and Ramón Castilla y Marquesado of the city of Iquitos, is very good 52.7% (79) in the case of male teachers while in The case of the female sex only reaches the good level 21.3% (32), which concludes that there is a difference of 11% between both sexes. Finally, the level of intercultural communication, in teachers of the educational institutions, Maynas and Ramón Castilla and Marquesado de Iquitos, is very good 37.3% (56).